1995
DOI: 10.1084/jem.181.1.429
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid residues required for binding of lymphocyte function-associated antigen 3 (CD58) to its counter-receptor CD2.

Abstract: Efficient activation and regulation of the cellular immune response requires engagement of T cell accessory molecules as well as the antigen-specific T cell receptor. The lymphocyte function-associated antigen (LFA) 3 (CD58)/CD2 accessory pathway, one of the first discovered, has been extensively characterized in terms of structure and function of the CD2 molecule, which is present on all T lymphocytes and natural killer cells of the human immune system. The binding site of human CD2 for LFA-3 has been localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
(33 reference statements)
0
14
0
Order By: Relevance
“…Prior studies have shown that the N-terminal membrane distaldomain (D1) mediates the adhesion function of the molecule by binding to the relevant counterreceptor (Sayre et al, 1989;Recny et al, 1990). Mutational analysis of human CD2 has demonstrated that the CD58 binding surface is located on the highly charged GFCC'C" face of the protein (Peterson & Seed, 1987;Arulanandam et al, 1993b;Somoza et al, 1993;Osborn et al, 1995). Notably, this same surface area forms a homodimeric contact in the crystal structures of rat and human CD2 (Jones et al, 1992;Bodian et al, 1994).…”
Section: Introductionmentioning
confidence: 93%
“…Prior studies have shown that the N-terminal membrane distaldomain (D1) mediates the adhesion function of the molecule by binding to the relevant counterreceptor (Sayre et al, 1989;Recny et al, 1990). Mutational analysis of human CD2 has demonstrated that the CD58 binding surface is located on the highly charged GFCC'C" face of the protein (Peterson & Seed, 1987;Arulanandam et al, 1993b;Somoza et al, 1993;Osborn et al, 1995). Notably, this same surface area forms a homodimeric contact in the crystal structures of rat and human CD2 (Jones et al, 1992;Bodian et al, 1994).…”
Section: Introductionmentioning
confidence: 93%
“…The inclusion of K87 in the interface only requires slight adjustment of the sCD2 lattice model, as noted (25), and the sidechain of K30 lies beneath the CCЈ loop, where it could affect CD2 binding indirectly. Thus, only D84, for which the mutagenesis data are, in any case, discordant (25,26), lies well outside the region of contact and seems unlikely to have a role in binding.…”
Section: Expression and Functional Analysis Of A Crystallizablementioning
confidence: 99%
“…On docking the CD2 and CD58 V-set domains in an orientation based on homodimeric, orthogonal lattice contacts observed in crystals of human sCD2 (Fig. 5A), all but three (K30, K87, and D84) of the residues implicated in the mutational analyses of CD58 (25,26) can, by selecting alternative sidechain rotamer conformations, be brought within binding- Fig. 3 A and B, respectively.…”
Section: Expression and Functional Analysis Of A Crystallizablementioning
confidence: 99%
“…Based on the solved structures of the adhesion domain of human CD2 (1dCD2) (Wyss et al ., 1995), a molecular model of wild‐type 1dCD58 has been constructed (Arulanandam et al ., 1994). The results of alanine scanning (Arulanandam et al ., 1994; Osborn et al ., 1995) suggest that the CD2‐binding epitope on CD58 can be mapped to the GFCC′C″ face analogous to the CD58‐binding site of CD2 (Arulanandam et al ., 1993b; Somoza et al ., 1993). Accordingly, five surface‐exposed hydrophobic residues that are not involved in the binding function initially were identified from a total of 33 hydrophobic residues (excluding proline and glycine) in 1dCD58 (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Although structural details of the human CD2 adhesion domain have been available through both NMR and X‐ray crystallography studies (Withka et al ., 1993; Bodian et al ., 1994; Wyss et al ., 1995), modeling of the CD2–CD58 interaction has been hindered by the lack of structural knowledge about the CD58 adhesion domain. The overall fold of the CD58 adhesion domain was predicted to be an immunoglobulin variable domain fold, and the ligand‐binding site was mapped to the GFCC′C″ face, similar to the adhesion domain of CD2 according to mutagenesis studies (Arulanandam et al ., 1994; Osborn et al ., 1995). However, the details about the amino acid residues involved in binding still await the experimental determination of the CD58 structure.…”
Section: Introductionmentioning
confidence: 99%